2014
DOI: 10.1073/pnas.1404082111
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Identification of gene ontologies linked to prefrontal–hippocampal functional coupling in the human brain

Abstract: Significance This study combines neuroimaging and whole-genome genotyping techniques with a gene set enrichment analysis to unravel the genetic basis of a well-validated intermediate phenotype for schizophrenia, dorsolateral prefrontal cortex–hippocampal connectivity. We found significant enrichment of genes with roles in synaptic plasticity and neurodevelopment that are consistent with the neurobiological basis of prefrontal–hippocampal interactions in schizophrenia. We further provide additional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
(119 reference statements)
0
5
0
1
Order By: Relevance
“…Copeptin is correlated with severity of the illness and is presumed to be a prognostic measure of outcome prediction in acute illness (Katan and Christ-Crain, 2010 ). Postoperative plasma copeptin level can be an independent predictor of POD and POCD after coronary artery bypass graft surgery (Dixson et al, 2014 ). This study observed higher levels of postoperative copeptin in POD and POCD patients compared to controls.…”
Section: Common Biomarkers Of Postoperative Delirium and Cognitive Dymentioning
confidence: 99%
“…Copeptin is correlated with severity of the illness and is presumed to be a prognostic measure of outcome prediction in acute illness (Katan and Christ-Crain, 2010 ). Postoperative plasma copeptin level can be an independent predictor of POD and POCD after coronary artery bypass graft surgery (Dixson et al, 2014 ). This study observed higher levels of postoperative copeptin in POD and POCD patients compared to controls.…”
Section: Common Biomarkers Of Postoperative Delirium and Cognitive Dymentioning
confidence: 99%
“…Other methods suffer from limitations such as requiring access to participants' genotypes, 17 and other methods fail to account for linkage disequilibrium (LD) that can lead to the same SNP being counted multiple times within a single gene set. 18 Here, we make use of a recently developed method, stratified linkage disequilibrium score regression, 19 that requires access to only genome-wide association summary level data. This method utilizes information from each SNP in a functional category while explicitly modelling LD to show whether a category is associated with a greater proportion of the heritability of a trait than the proportion of SNPs it contains would suggest.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of VGCC genes has also been reported in large-scale genomic studies of BD-relevant phenotypes, such as working memory performance and the associated patterns of brain activation [36] , as well as in general cognitive functioning [37] . There are also smaller candidate gene studies that suggest effects of CACNA1C genetic variation on brain imaging phenotypes 38 , 39 and on cognitive domains, such as reward responsiveness [40] .…”
Section: Calcium Signalling In Bipolar Disorder: Linking Genetics Pamentioning
confidence: 99%